2009
DOI: 10.1111/j.1528-1167.2008.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific plasticity in the epileptic rat brain: A hippocampal and extrahippocampal analysis

Abstract: SUMMARYPurpose: Recent evidence suggests that aberrant neuro/gliogenesis and/or inflammation play critical roles in epileptogenesis. Although the plastic and inflammatory changes have been described in the postseizure hippocampus, little data is available concerning extrahippocampal regions, notably in the piriform and entorhinal cortices, amygdala, and parts of the thalamus. In this study, we examined histological changes in whole epileptic rat brain, with respect to cell death, cell genesis, and inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 40 publications
7
42
0
1
Order By: Relevance
“…Since increased GABA release in the DG during the early post-seizure period was thought to regulate the proliferation and survival of newborn neurons, SDF-1 may promote the proliferation of newborn neurons through augmentation of the GABAergic inputs during the seizures. The SDF-1 protein level has been shown to be significantly increased as early as 24 h after SE, and this elevation can last for 1 month (Jung et al 2009). Similarly, in the present study, we found the expression of SDF-1 and CXCR4 recovered at the baseline levels on 42 days after KA injection by western blot analysis, while EE for 30 days could delay the attenuation of the expression of SDF-1 and CXCR4.…”
Section: Effects Of Ee On Aberrant Hippocampal Neurogenesis and The Esupporting
confidence: 73%
See 2 more Smart Citations
“…Since increased GABA release in the DG during the early post-seizure period was thought to regulate the proliferation and survival of newborn neurons, SDF-1 may promote the proliferation of newborn neurons through augmentation of the GABAergic inputs during the seizures. The SDF-1 protein level has been shown to be significantly increased as early as 24 h after SE, and this elevation can last for 1 month (Jung et al 2009). Similarly, in the present study, we found the expression of SDF-1 and CXCR4 recovered at the baseline levels on 42 days after KA injection by western blot analysis, while EE for 30 days could delay the attenuation of the expression of SDF-1 and CXCR4.…”
Section: Effects Of Ee On Aberrant Hippocampal Neurogenesis and The Esupporting
confidence: 73%
“…The dead or injured neurons, reactive glial cells, and endothelial cells have been reported to release SDF-1 after brain injury such as stroke or seizures (Schonemeier et al 2008;Jung et al 2009). SDF-1/CXCR4 plays a particularly important role in adult neurogenesis and synergistically influences the GABAergic synaptic inputs to DG neural progenitors then modulates the neurogenesis of the DG directly (Bhattacharyya et al 2008).…”
Section: Effects Of Ee On Aberrant Hippocampal Neurogenesis and The Ementioning
confidence: 99%
See 1 more Smart Citation
“…Silencing of the same population of GABAergic medial septal neurons in nonepileptic animals greatly diminishes theta oscillations (22). There is also a loss of neurons in the entorhinal cortex (40,61), with detailed studies showing loss of dorsal layer III medial entorhinal cortex neurons that form the temporoammonic input to the lacunosum moleculare layer in epileptic animals (40) and human TLE (62). This loss, when combined with the expansion of the perforant path, may mediate some of the alterations of theta power and coherence in the hippocampus (40), as well as changes to theta phaseprecession (58).…”
Section: Theta Rhythmopathy In Models Of Epilepsy: Potential Causesmentioning
confidence: 99%
“…SDF-1/ CXCR4 plays particularly important roles in adult neurogenesis through mediating the proliferation of neuroprogenitor cells, regulating the migration, differentiation, and functional integration of newborn neurons into existing neuronal networks [11][12][13]. There was evidence showing that SDF-1 protein levels were increased after status epilepticus (SE) in the hippocampus, which was associated with cell genesis [14]. Therefore, SDF-1/CXCR4 pathway may be involved in the altered microenvironments of newborn neurons after seizures.…”
mentioning
confidence: 99%